The db/db Mouse: A Useful Model for the Study of Diabetic Retinal Neurodegeneration - Bogdanov, Patricia; Corraliza, Lidia; A. Villena, Josep; Carvalho, Andrea R.; Garcia-Arumí, José; Ramos, David; Ruberte, Jesús; Simó, Rafael; Hernández, Cristina (PLOS ONE, 2014)
Background To characterize the sequential events that are taking place in retinal neurodegeneration in a murine model of spontaneous type 2 diabetes (db/db mouse). Methods C57BLKsJ-db/db mice were used as spontaneous type 2 diabetic animal model, and C57BLKsJ-db/+ mice served as the control group. To assess the chronological sequence of the abnormalities the analysis was performed at different ages (8, 16 and 24 weeks). The retinas were evaluated in terms of morphological and functional abnormalities [electroretinography (ERG)]. Histological markers of neurodegeneration (glial activation and apoptosis) were evaluated by immunohistochemistry. In addition glutamate levels and glutamate/aspartate transporter (GLAST) expression were assessed. Furthermore, to define gene expression changes associated with early diabetic retinopathy a transcriptome analyses was performed at 8 week. Furthermore, an additional interventional study to lower blood glucose levels was performed. Results Glial activation was higher in diabetic than in non diabetic mice in all the stages (p<0.01). In addition, a progressive loss of ganglion cells and a significant reduction of neuroretinal thickness were also observed in diabetic mice. All these histological hallmarks of neurodegeneration were less pronounced at week 8 than at week 16 and 24. Significant ERG abnormalities were present in diabetic mice at weeks 16 and 24 but not at week 8. Moreover, we observed a progressive accumulation of glutamate in diabetic mice associated with an early downregulation of GLAST. Morphological and ERG abnormalities were abrogated by lowering blood glucose levels. Finally, a dysregulation of several genes related to neurotransmission and oxidative stress such as UCP2 were found at week 8. Conclusions Our results suggest that db/db mouse reproduce the features of the neurodegenerative process that occurs in the human diabetic eye. Therefore, it seems an appropriate model for investigating the underlying mechanisms of diabetes-induced retinal neurodegeneration and for testing neuroprotective drugs.